Desentralisasi Fiskal Dan Disparitas Regional Di Provinsi Riau - Mardiana '; Syafril Basri (Jurnal Ekonomi, 2012)
This study is to identify the economic growth of oil-gas producing region and non-producing; examine regional disparities resulting from decentralization; and identify sources of disparities. This study uses GDP and population data districts and cities in the Province of Riau in 2001 to 2010. Analysis tools in the study is the pattern of growth, the Williamson coefficient of variation and T-Theil decomposition.  Regions not receiving funds from oil and gas tend to be more developed with average growth and high income. In the period 2000- 2010 only Pekanbaru are classified as the developed region of the receiving the oil and gas receiving fund. Following the decentralization of fiscal, income disparities between regions in Riau declined until 2006, and increased again until 2009. Disparity back in 2010 has decreased. Source's disparity, mainly due to income inequality among regions within a group, not because between group's gas and oil fund receiving with the non-receiving group. Source of disparity biggest between regions in the group's oil funds receiving.